Propriedades das raízes verbais em mundang (Família Niger-Congo) - Véronique Douzaka Pahimi (2021)
The purpose of this dissertation is to contribute to a more refined knowledge about one of the languages of the Adamawa-Ubangui linguistic group, the Mundang, which already has a reference grammar, written by Elders (2000). The objective is to contribute to a morphosyntactic description of Mundang, investigating if its linguistic data corroborate the hypothesis about the classification of verbal roots, as is proposed by Schäfer (2008). This author assumes the theoretical proposal, according to which verbal roots present lexical entry that can inform if a certain verb undergo the causative alternation or not. More specifically, we intend to identify the following properties: (i) if agentive verbs only accept a controlling agent in its subject position and do not undergo causative alternation; (ii) if verbs of external causation accept agents and causers as subjects, and if they undergo alternation or not; (iii) if only roots of unspecified cause undergo causative alternation; and (iv) if roots of verbs of internal cause do not form direct causatives in Mundang, but only inchoatives instead. The data collection was taken remotely, by means of elicitation with four informants, proposing a set of sentences with different kinds of verbal roots. Considering the data collected, we established that verbs of unspecified cause are the only verbs of change of state that undergo alternation in Mundang, according to what is proposed in Schäfer (2008). It was also observed that the external argument in agentive roots is occupied by Voice [+AG] with or without control. Furthermore, we conclude that verbs of external cause do not allow the anticausative alternation and verbs of internal cause cannot be transitivized.